زوجہ کا حقِ نفقہ: منتخب اردو تفاسیر اور مروجہ پاکستانی قوانین کا مطالعہ: Wife’s right to Nafaqah: A Study of selected Urdu Commentaries of the Quran and Existing Pakistani Laws - Hafiz Falak Shair Faizi; Dr.Muhammad Hasib (Al-Qamar, 2019)
This paper studies wife’s right to Nafaqah in the light of selected Urdu Commentaries of the Quran and Existing Pakistani laws. It finds that there are some differences between Urdu commentaries and Pakistani law on Nafaqah, but as a whole the two are mutually exclusive. To all provision of Nafaqah is woman’s right; husband will keep the wife where he resides; he is responsible for her food and clothing. If a divorced woman asks for a wage to breastfeed the child, husband has to pay her. The wife can sue for the provision of Nafaqah and make this right possible through the law. However woman’s right to Nafaqah is due to the obedience that she voluntarily performs with her husband. If she does not remain bound to live with her husband, her right to Nafaqah will be revoked. As for the status of the husband in this regard is concerned, it will be decided keeping in view the relevant circumstances.